Pandangan Dosen PTKI Di Madura Terhadap Formula Ijtihad Muhammad Bin Abdul Wahhab - A. Ghufran Ferdiant; Mohammad Bashri Asyari (UIN Mataram, 2020)
Lecturers as academics, educators, researchers and actors of community service are seen as groups of people who have a deeper ability to research and objectively examine the products of contemporary renewal thinking according to their competence and have the opportunity to disseminate them to the wider community. sufficient access in influencing the public's understanding and views of issues of contemporary renewal thinking, especially those that are still considered controversial, such as the views of ijtihad Muhammad Ibn Abd. Wahhab. This article used descriptive field research to examined the views of PTKAI lecturers in Madura to find out their knowledge of the Ijtihad Muhammad bin Abdul Wahhab formula with the title